Dynamics of motorized momentum exchange tether for payloads capture. Issue 9 (1st May 2017) - Sun, Qilong; Liu, Yanfang; Qi, Naiming; Yang, Yong; Chen, Zhenpeng
Abstract: The dynamics of motorized momentum exchange tether (MMET) during and after payloads capture is studied. The ideal velocities of payloads with same mass for capture are analyzed, and a mathematical model of capture is proposed. If the MMET captures the payloads at the ideal velocity, the MMET's orbit and motion state are unchanged. However, considering that capture velocity error exists in practice, and analyzing the velocity error in relation to the payload approaching from the earth as an example, the impact on the MMET's orbital parameters and state motion are investigated during payload capture for different capture velocity errors, including errors in magnitude and direction. The simulation results show that if the payload velocity has only magnitude error, the perigees remain overlapping and the semi-major axes of the changed orbits also continue to coincide after capture; however, the changes in other orbital parameters are approximately proportional to the error. If the payload velocity has both magnitude and direction errors, then all of the orbital parameters change, including the perigee and the direction of the semi-major axis. However, the normal velocity increment caused by the capture's normal velocity error changes the orbital parameters far less than the tangential velocity increment.